Colonic intussusception in the adult About 2 cases. - Cardozo, Sandra; Santiago, Pablo; Barberousse, Carlos; Canessa, César; Colet, Andrés (Cirugía del Uruguay, 2006)
The paper reports 2 clinical cases of colonic invagination in adults with comments as to its physiopathology, etiology, and treatment. The pathology is relatively rare in adults, and is generally due to neoplassic causes. CAT scan is the elective tool for diagnosis and resection the preferred treatment.